Effectiveness and easiness of adherence to behavioural guidelines for diet and lifestyle changes for cholesterol‐lowering: the Increasing Adherence of Consumers to Diet & Lifestyle Changes to Lower (LDL) Cholesterol (ACT) randomised controlled trial. Issue 5 (27th May 2019) - Magriplis, E.; Sialvera, T. E.; Papadopoulou, A.; Efstathiou, S. P.; Trautwein, E. A.; Goumas, G.; Dimakopoulos, I.; Papavasiliou, K.; Koutsouri, A.; Zampelas, A.
Abstract: Background: The present study aimed to assess perceived effectiveness and easiness of behavioural diet and lifestyle changes related to dyslipidaemia given by physicians or dieticians as a result of diet and lifestyle modifications being difficult to maintain. Methods: One‐hundred hypercholesterolaemic individuals were enrolled in a parallel, randomised 6‐week study. Fifty were advised by dietitians (dietitian group: DG) in six weekly face‐to‐face behavioural therapy sessions and 50 received standard advice from physicians (physician group: PG). All individuals were followed‐up for another 6 weeks under real‐life conditions. Questionnaires regarding perceived effectiveness, easiness of adhering, forecasted and actual adherence to specific cholesterol‐lowering advice were completed. Results: Scores of perceived effectiveness of advice for sufficient exercise, limiting saturated fat (SFA) intake, eating fish twice a week, consuming plenty of fresh fruit and vegetables, and limiting salt intake different scientifically (all P < 0.05) in PG and DG between study phases. Scores of the individuals' perception of effectiveness at all study phases were higher in the DG compared to PG for sufficient exercise, limiting SFA intake, eating fish twice a week, eating plenty of fruits and vegetables, and limiting salt intake, whereas scores of easiness were significant only for fish consumption ( P = 0.008) and using foods with added plant sterols (all P < 0.05). DG and PG significantly differed in forecasted (week 6) versus actual adherence (week 12) to various chances, with DG reporting higher adherence. Conclusions: Lifestyle and dietary changes related to dyslipidaemia can be achieved with continuous education, monitoring and follow‐ups by dieticians, as well as potentially other trained healthcare professionals.